The effect of fatigue on frontal plane angular changes in the lumbar spine of elite rowers. Issue 4 (27th March 2011) - Wilson, F; Simms, C; Gormley, G; Gissane, C
Abstract : Background: The incidence of lumbar spine injury is high in rowers. Spinal kinematics and fatigue may influence onset of this injury. Objective: To quantify lumbar spine motion in the frontal plane (at L3) and examine the effects of fatigue (measured by changes in blood lactate accumulation) on changes in angular displacement of the lumbar spine during ergometer rowing. Design: The lumbar spine kinematics of the study cohort were measured using a Spectrotilt Inclinometer connected to a Biometrics DataLog system. Setting: A laboratory based study of elite level rowing. Participants: 12 elite rowers, all male, mean age 23.2 (5.2) years, mean weight 79.1 (5) Kg. Assessment of risk factors: Lumbar spine angular kinematics were measured in the frontal plane at L3 during an ergometer rowing trial. The trial was an incremental 'step test' on a Concept 2 ergometer. Blood lactate was sampled at 3 min intervals throughout the test using a portable lactate analyser. Main outcome measurements: Changes in spinal angular displacement between the first and last stage of the test. Fatigue was indicated by accumulation of blood lactate. Results: Mean angular displacement was 4.6° (1.4) at the first stage of the test, increasing to 8.7° (2.1) for the last stage. A significant increase in frontal plane angular displacement between the first and last stage of the test was observed (mean increase=4.1° (1.94), 95% CI 2.9 to 5.3°, t=7.36, p=0.000014). Incremental rise in angular displacement was associated with an incremental rise in blood lactate. Conclusion: The high values of angular displacement reached by the participants in this study confirm that there is considerable frontal plane motion during rowing and this increases with fatigue and should be considered as a factor for injury.